Paradigmatic Study of the Regulation for Acceleration of Information Technology-Based Tax Dispute Resolution in Indonesia - Prabowo, Bagus Harie (Universitas Pelita Harapan, 2025)
The increasing number of tax disputes in Indonesia has created a new problem in the form of tax uncertainty, which this research aims to resolve through a paradigmatic study based on the participatory paradigm in normative studies with empirical support related to regulations and practices, to accelerate tax dispute resolution. Through the self-assessment process, taxpayers are required to register themselves, followed by calculating, paying, and reporting taxes. During the supervision of this process, tax officials can conduct audits that culminate in the issuance of tax assessments, which can trigger disputes. The resolution of tax disputes begins with the administrative stage through a quasi judicial institution called objections under the tax authority, with further legal efforts in the form of litigation at a judicial institution called the Tax Court, where the decision is final and binding, up to extraordinary legal efforts through judicial review to the Supreme Court. Resolving tax disputes can be interpreted as preventing the occurrence of, or resolving existing, tax disputes. Meanwhile, the acceleration of tax dispute resolution, as referred to in the research assumptions, can be interpreted as an effort to improve the quality of tax dispute resolution, in terms of time and decision, thereby reducing further legal efforts. On the other hand, information technology is increasingly developing and promises to accelerate tax dispute resolution. Various information technologies, such as digitalization, the Internet of Things, big data, blockchain, and even artificial intelligence, when used appropriately, have been proven to provide the necessary acceleration in tax dispute resolution. This study concludes with an analysis of the ideal arrangement for accelerating tax dispute resolution based on information technology, through analyzing the gap between current regulations and practices in tax dispute resolution.